2011
DOI: 10.1080/1389224x.2011.536340
|View full text |Cite
|
Sign up to set email alerts
|

Acting as a Change Agent in Supporting Sustainable Agriculture: How to Cope with New Professional Situations?

Abstract: How do change agents deal with the diversity of farmers' attitudes towards the future of agriculture? How do they themselves cope with change and understand their role as change agents? We chose a comprehensive, action-training approach to answer such questions and worked with agents belonging to two different extension networks. The agents acknowledged their historically built professional models and discussed their professional situations in relation to the need to develop new skills and to address new audie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 12 publications
(19 reference statements)
3
29
0
5
Order By: Relevance
“…Today's advisors are increasingly becoming facilitators who support farmers' transformative agency towards agricultural innovation instead of merely disseminating information and telling farmers what to do in regard to operational-tactical issues (Dogliotti et al, 2013;Ingram, 2008;Kilelu et al, 2014). Such a change in the advisor's role require new tools, new ways of knowing and new ways of relating, through knowledge exchange encounters with clients (Cerf et al, 2011;Ingram, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Today's advisors are increasingly becoming facilitators who support farmers' transformative agency towards agricultural innovation instead of merely disseminating information and telling farmers what to do in regard to operational-tactical issues (Dogliotti et al, 2013;Ingram, 2008;Kilelu et al, 2014). Such a change in the advisor's role require new tools, new ways of knowing and new ways of relating, through knowledge exchange encounters with clients (Cerf et al, 2011;Ingram, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…They must creatively apply the tools of their trade and develop new production routines" (Wolf, 2008: 205). In the case of advisory professions, such new production routines might include obtaining knowledge to offer adequate advisory services for the different types of queries clients have and developing new advisory services which meet the emerging needs of clients due to changing circumstances (Albaladejo et al, 2007;Cerf et al, 2011). There is a parallel here with knowledge intensive business service firms (KIBS), which have been defined as private companies or organisations relying heavily on professional knowledge (i.e.…”
Section: Advisors' Knowledge Exchange Interfaces: Forms and Risksmentioning
confidence: 97%
“…In some places, such brokers are already operational (Klerkx and Leeuwis, 2008;Klerkx and Jansen, 2010). However, as regards the challenge for the advisors to obtain the knowledge to offer adequate advisory services, there has been far less attention to how the different advisory professions within the land management advisory system might do this themselves (notable exceptions include Albaladejo et al, 2007;Höckert et al, 2010;Cerf et al, 2011, who studied identity development, learning and collaboration of advisors). Indeed, it has been indicated that more research is needed (Ingram and Morris, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…The farmers' board and the managers of the Chamber of Agriculture proposed to hire a new advisor (B.O) to provide advice to the farmers who were contracted to reduce the use of inputs; the intermediary in this case. This case study is based on a longitudinal approach of tracking advisors as practitioners of change (Maxime et al, 2002;Cerf et al, 2011) and explains the specific role of the B.O. in networking various activity systems at both local and national levels in order to support the search and development of on-farm pathways towards sustainability.…”
Section: Presentationmentioning
confidence: 99%